Tecnologias habilitadoras da indústria 4.0 aplicadas para melhoria da segurança do trabalho na construção civil - Soares Júnior, Gilberto Gomes (2021)
The work aims to identify how the enabling technologies of Industry 4.0 can be applied to improve job security in civil construction, since companies in the civil construction sector are seeking to improve and develop work to reduce risks and accidents. The methodology was developed based on the literature review related to the theme, and on field research, and the data collection took place, through a field research with 8 specialists in the construction sector, with application a 5-point Likert scale questionnaire to identify the possibility of improving work safety in civil construction, using the technologies of Industry 4.0. The results of this research pointed out that the main technologies listed for improving work safety for construction were: (1st) 3D printer and drone, (2nd) augmented reality and wearable sensors, (3rd) safety vest, (4th) reality virtual, (5th) bionic exoskeleton, (6th) BIM, RFID, helmet with sensors and smart helmets, (7th) Internet of things and finally, (8th) concrete mixer truck. The contribution of this work is given by the presentation of technologies from Industry 4.0 that can maximize work safety in the construction industry, mitigating accidents at work, thus collaborating for the management of technology and innovation. For future work it is suggested to expand this research with more specialists, if possible from other states of the federation and also from other countries.